Ibn al-‘Arabi on Affirming the Oneness of Allah’s Divinity (al-Tawhid) - Badron, Mohd Sani (Afkar: Jurnal Akidah dan Pemikiran Islam, 2010)
Ibn al-‘Arabi explains that Allah states thirty-six times in the Qur’an that He is the only truly divine Deity (tawhid). Those verses comprehensively cover the faith and belief in Allah’s names and attributes. As specific ways to remember God (tahlil) and as descriptions of Who He is, all those verses are indeed a Mercy from Him to humanity in general and to those who truly submit to Him in particular.